(untitled) (Research, Society and Development, 2021)
The studies on the Pre-Calculus curricular component offered in the initial years of graduation, have been widely discussed in the academic environment, considering that the development of the component involves contents that require a conceptual basis of functions of logarithmic and exponential types contained in the content of mathematics applied in the final years of basic education. The objective was to reflect analytically the Pre-Calculus curricular component in its conceptual approaches in the Mathematics Degree Course, related to didactic practice in the teaching-learning process. It was used as methodology, the research of qualitative and quantitative nature, of descriptive, exploratory and analytical character. For data collection, a bibliographic survey was carried out, based on the criterion of updated publications, through the Scielo and Google Scholar platforms, considering the period of national and international publications between 2017 and 2021. The results demonstrated the learning difficulty in undergraduate courses that collaborates with dropouts and failures at the beginning of the course and indicated didactic practices that deserve attention in improvements that contribute to a conceptual basis in the final years of basic education. It can be concluded that the learning difficulties of the component in the initial years of graduation, indicate the need to rethink the didactic methods and practices of mathematical content since high school.